1993
DOI: 10.1007/bf00181711
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fresh autogenous with formalin preserved allogeneic bone grafts in rabbits

Abstract: A complete circumferential gap was produced in the diaphysis of the ulna in rabbits and the radius was left intact. The gap on the right side was filled with formalin preserved allogeneic (FPA) bone graft, and fresh autogenous bone taken from the right ulna was put into the gap on the left side. The gap was left untouched in a control group. Up to 8 weeks, the rate of union was slower in the FPA grafts compared with the autogenous grafts. Maximum fluorescence was seen at 10 to 16 weeks and was the same in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Integration of autologous cortical bone grafts of the diaphysis of the radius and ulna were observed on radiographs in other studies after six and sixteen weeks 22 , 31 . Although there is a close relationship between revascularization of the bone graft and its integration, it was shown that incorporation of the cortical bone graft was not expected, even when fixed in a stable manner to a healthy bed, with good vascularization.…”
Section: Discussionmentioning
confidence: 80%
“…Integration of autologous cortical bone grafts of the diaphysis of the radius and ulna were observed on radiographs in other studies after six and sixteen weeks 22 , 31 . Although there is a close relationship between revascularization of the bone graft and its integration, it was shown that incorporation of the cortical bone graft was not expected, even when fixed in a stable manner to a healthy bed, with good vascularization.…”
Section: Discussionmentioning
confidence: 80%
“…The rate of union using FPA was reported to be the same as autologous bone by Mehra et a/. 4 although the onset of union was delayed in FPA bone graft. We found our results with cancellous FPA bone graft comparable to autogenous bone graft.…”
Section: Discussionmentioning
confidence: 86%
“…The mechanism of action is believed to be protein molecule enlargement due to the reaction of formaldehyde with the reactive group of proteins>, Previous reports on the use of formalin preserved allograft have demonstrated its efficacy in animal models. Mehra et al 4 and Sharma et al 6 used FPA to bridge an osteoperiosteal gap in the ulnar diaphysis of rabbits. Gonzalves et al used it in the repair of mandibular defect in Wistar rats?…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that autologous bone grafts could provide healing of such a defect in a similar model. [25][26][27] We decided not to study a group with BMC alone because this cannot be used in clinical cases for such large defects of a long bone. The cell suspension needs a rigid scaffold or a gel to be maintained in the defect to avoid dispersion of the cells and formation of ectopic bone.…”
Section: Discussionmentioning
confidence: 99%